"Introducing Modified Dakkak and Bennett Grading System for Indian Food in Oral Submucous Fibrosis": A Dharwad Study. (4th March 2019) - Kalkur, Chaithra; Sattur, Atul P.; Guttal, Kruthika S.; Lakshman, Anusha R.
GRAPHICAL ABSTRACT: ABSTRACT: Oral submucous fibrosis (OSMF) is one of the "diseases of civilization" because of the large differences in prevalence among races, geographic areas, and individuals at different socioeconomic levels. It is a premalignant condition strongly associated with the habit of chewing areca nuts. This study is to compare the scoring system in relation to the burning sensation of mouth and dysphagia using the visual analog scale (VAS) and Dakkak and Bennett grading system for Indian food, respectively, in OSMF patients. This study was a randomized clinical trial incorporating a total of 50 cases of OSMF divided into a control group (antioxidant therapy) and pentoxifylline test cases. Values for burning sensation of the mouth using the VAS and modified Dakkak and Bennett grading system for Indian food were recorded. Statistical analyses were done using t test, Mann –Whitney U test, and one-way analysis of variance (ANOVA) test. Patients subjected to pentoxifylline when compared to the control group showed significant reduction in dysphagia for Indian food. Burning sensation was recorded according to the visual analogue scale. Significant reduction in burning sensation was seen in the pentoxifylline group when compared to the control group. This grading system provides quantitative and qualitative parameters in patients with OSMF.